2017
DOI: 10.3126/jist.v22i1.17735
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of Sinkholes Affected Area of Thulibeshi Phat, Armala, Kaski, Nepal

Abstract: The area affected by sinkholes in Thulibeshi Phat of Armala VDC, Pokhara was studied in order to understand natural settings of the study area. A total of 117 sinkholes from depth range of 1 to 5 m and diameters from 1 to 15.2 m were observed at the time of our field visit. Out of these sinkholes, 52 sinkholes were filled sinkholes, 12 were water-bearing sinkholes and others were opened sinkholes. The area consists of sediments of fluvio-lacustrine and debris deposits and the sinkhole site has sediments mainly… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 4 publications
0
6
0
Order By: Relevance
“…Similarly, various locations within the Pokhara-Lekhnath Metropolitan City have experienced land subsidence. Pokhrel [54], Rijal [55], and Rimal et al [8] have reported the highly susceptible areas to land subsidence.…”
Section: Land Subsidence and Sinkholementioning
confidence: 99%
See 2 more Smart Citations
“…Similarly, various locations within the Pokhara-Lekhnath Metropolitan City have experienced land subsidence. Pokhrel [54], Rijal [55], and Rimal et al [8] have reported the highly susceptible areas to land subsidence.…”
Section: Land Subsidence and Sinkholementioning
confidence: 99%
“…Land collapse, land subsidence, and sinkhole hazards are most prominent within Pokhara City [54]. Thulibesi phant in Armala, where 117 sinkhole spots were observed, is exposed to severe sinkhole hazards [55]. Sarangakot and Kaskikot within the Phewa watershed [56] and the Rupakot area of the Rupa watershed [57] are prone to landslide hazards.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The frequent naturally-occurring of sinkholes changing the different land use patterns and overall decreasing overall productivity (Rijal, 2017). The problem arises from the hazardous expansion of the urban centre, lacking standard norms and regulations, improper spatial planning and unwanted population growth is the need of the present time.…”
Section: Introductionmentioning
confidence: 99%
“…In the study conducted in the land subsidence site of Armala, Kaski, Nepal; it was mentioned that water chemistry depends upon the surrounding rocks of sub-surface water (Rijal, 2017). Additionally, Gautam and Bhattarai (2008) suggested that the physical and chemical characteristics of waters in reservoirs were influenced by seasonal fluctuations in water and also by agricultural runoff.…”
Section: Introductionmentioning
confidence: 99%